2012
DOI: 10.1111/j.1467-8535.2012.01285.x
|View full text |Cite
|
Sign up to set email alerts
|

A knowledge engineering approach to developing educational computer games for improving students' differentiating knowledge

Abstract: Educational computer games have been recognized as being a promising approach for motivating students to learn. Nevertheless, previous studies have shown that without proper learning strategies or supportive models, the learning achievement of students might not be as good as expected. In this study, a knowledge engineering approach is proposed for developing educational computer games to help students learn about the knowledge for differentiating a set of learning targets in an interesting and meaningful way.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 39 publications
4
33
0
1
Order By: Relevance
“…Sin embargo, para alcanzar resultados exitosos en el plano educativo es necesario contar con una planificación adecuada e implementar estrategias pertinentes que faciliten la comprensión de los contenidos por parte del estudiantado; todo lo anterior adaptado a un marco educativo que, fuera de exitoso, sea congruente con los objetivos pedagógicos, y que, además, mejore las competencias cognitivas [23][24][25].…”
Section: Videojuegos En La Educaciónunclassified
“…Sin embargo, para alcanzar resultados exitosos en el plano educativo es necesario contar con una planificación adecuada e implementar estrategias pertinentes que faciliten la comprensión de los contenidos por parte del estudiantado; todo lo anterior adaptado a un marco educativo que, fuera de exitoso, sea congruente con los objetivos pedagógicos, y que, además, mejore las competencias cognitivas [23][24][25].…”
Section: Videojuegos En La Educaciónunclassified
“…That is why, it is important to promote students' learning motivation in order to improve their learning achievement of defence science courses. Several recent studies have also reported that educational computer games have the potential of promoting students' learning motivation, which could result in good learning achievement (Burguillo, 2010;Liu and Chu, 2010;Dickey, 2010;Houssart and Sams, 2008;Huang et al, 2010;Hwang et al, 2013b;Sung and Hwang, 2013;Khamparia and Pandey, 2015a). Students' self-efficacy and deducing anxiety have been recognised as important factors to be considered in educational settings (Li et al, 2011;Hwang et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…The use of collaborative systems has yielded major improvements in, for instance, reducing replications within systems [3,7]. Whilst games have been used widely as a paradigm for learning and education [8,9], recent studies reveal that whilst computer games in general have the potential to enhance learning interest and increase motivation [10][11][12], non-collaborative games may yield a negative impact on learning outcomes and self-alienation [10,[13][14][15][16]. These studies highlight the importance of collaborative games and their strength in comparison to the more traditional non-collaborative games.…”
Section: Introductionmentioning
confidence: 99%